Experimental infection of Crested Caracara (Caracara plancus) with Toxoplasma gondu simulating natural conditions - Vitaliano, S. N. [UNESP]; Mineo, T. W. P. [UNESP]; Andre, M. R. [UNESP]; Machado, R. Z. [UNESP]; Mineo, J. R.; Werther, K. [UNESP] (Elsevier B.V., 2010)
Toxoplasma gondu affects mainly warm-blooded animals including birds Even though previous experimental data indicate that raptors are resistant to clinical infection there is no information regarding the susceptibility of Brazilian birds of prey to T gondii The present study aimed to observe how the crested caracara a common raptor in Brazil Interacts with T gondu, using an experimental model Seven crested caracaras seronegative for T gondu were separated into infected (n = 5) and control groups (n = 2) Birds from the infected group were fed T gondu-Infected Calomys callosus a rodent present in Brazilian savanna and described as highly susceptible to infection by the parasite for three consecutive days while control animals were fed non-Infected rodents All Infected birds produced T gondu-specific IgG antibodies that were firstly detected at day 7 post-Infection with peak production detected between 15 and 30 dpi No significant alterations in clinical and hematological parameters were observed throughout the experimental period and parasites were sparsely found in muscular tissues after the birds were euthanized In conclusion our results demonstrated that crested caracaras are resistant to oral infection with T gondu suggesting that the host-parasite relationship between both species has reached a remarkable equilibrium (C) 2010 Elsevier B V All rights reserved
Keywords: Toxoplasma gondu; Raptors; crested caracara; IgG antibody; Experimental infection